ARTIFICIAL INTELLIGENCE AND 3D TECHNOLOGIES INTEGRATION FOR DEVELOPING COMPLEX METHODOLOGICAL SUPPORT FOR HYDROCARBONS AND DIDACTIC PRINCIPLES (International Conference on Modern Science and Scientific Studies, 2025)
This research analyzes the principles and practical results of developing complex methodological support for hydrocarbons based on the integration of artificial intelligence and 3D visualization technologies. The study develops didactic foundations for integrating modern educational technologies into chemistry education. The methodological support includes AI-based adaptive learning systems, 3D molecular modeling tools, augmented reality (AR) and virtual reality (VR) applications, gamification elements, and formative assessment mechanisms. The developed didactic principles and methodology serve to improve the quality of chemistry teaching in secondary education institutions and develop students' 21st-century skills.